(untitled) (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study aims to examine the types and functions of code-switching and code-mixing in the lyrics of the female vocal group TWICE’s maxi-single “One More Time.” This study employs the theory of code-switching by Chaer and Agustina, the theory of types of code-switching by Poplack, and the theory of code-mixing by Kridalaksana and the theory of code-mixing types by Muysken, and Barthes’s theory of connotative and denotative meaning. The data, consisting of song lyrics, were collected through the listening method using note-taking techniques and then analyzed using the intralingual equivalence method. The results of the study revealed 12 instances of codeswitching, including intrasentential code-switching and tagging, with a predominance of intrasentential code-switching and no instances of intersentential code-switching. In addition, 7 instances of code-mixing were found in the form of word insertion and phrase insertion, without any congruent transitions or lexicalization. These findings indicate that codeswitching and code-mixing serve to emphasize meaning, strengthen emotional expression, adapt to musicality, and construct a modern and global image. Thus, the use of multilingualism in song lyrics is not only aesthetic but also communicative in reaching a multilingual audience.